PENGARUH INFLASI DAN SUKU BUNGA TERHADAP INVESTASI DALAM NEGERI DI INDONESIA - Samuel Richard Messakh; Paulina Yuritha Amtiran; Marselina Ratu (Universitas Nusa Cendana, 2019)
The purpose of this study to determine the effect of inflation and interest rates partially andsimultaneously to domestic investment in Indonesia. This research is quantitative descriptive. Thedata used in the research are secondary data on inflation, interest rate and domestic investmentsourced from Bank Indonesia and Central Bureau of Statistics from 2000-2016. Data analysistechnique in this research is Multiple Linear Regression Analysis. Based on regression analysis, itis known that inflation has a positive and insignificant effect on domestic investment in the period of2000-2016. Meanwhile, interest rates has a negative and significant effect on domestic investment inIndonesia. In addition, inflation and interest rates also together affect the domestic investment inIndonesia in the period 2000-2016. Keywords : Inflation, Domestic Investment, Investment, Interest Rate